Surviving as a Vegan in a World of Omnivores: Relational Fractures in Shared Practices - Aboelenien, Aya; Arsel, Zeynep (Journal of Consumer Research, 2026)
Abstract Prior research documents the role of the misalignment of practice elements in practice habituation and change. We extend this literature by demonstrating the understudied role of practice relationality. Locating our empirical work in veganism, a context that encompasses a bundle of interrelated practices, we show how people who adopt veganism manage the relationality of their food-related practices (e.g., eating, cooking, and shopping for food) during shared moments. Building on interview, secondary, and netnographic data on people who pursue veganism, we demonstrate that changes in shared practice performances cause relational fractures. We pinpoint relational fractures that hinder practitioners from smoothly performing shared practices in three contexts: co-performance, co-learning, and the marketplace. To repair practice relationality, vegan consumers enact four relational competences: decoding, decoupling, divesting, and chameleoning. These competences can repair some relational fractures while aggravating others. When vegan consumers fail to acquire any competence, however, they revert to their old omnivorous performances. Our article contributes to practice theory by conceptualizing the role of practice relationality in practices, introducing the concept of relational competence as a necessary element for performance (re)rehabituation, and demonstrating the role of practice intelligibility in the co-performance of shared practices.